The Poncokusumo Village Information System In The Context Of Moving Towards A Digital Village - Arief Andy Soebroto; Agi Putra Kharisma; Diva Kurnianingtyas; Syakirah Dwi Anisa; Charles Eugene; Annisa Indah Fitriani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Manual administrative processes in Poncokusumo Village have long been a source of inefficiency, resulting in common problems such as service delays, restricted public access to information, and difficulties with data archiving. To tackle these issues, this study set out to analyze the impact of the Sistem Informasi Manajemen Desa/Kelurahan (SIMDEK) on the effectiveness of village administration. The research employed the Community-Based Participatory Action Research (CBPAR) method, utilizing a combination of questionnaires and the Wilcoxon test to assess the understanding of the SIMDEK website among village officials and residents. The primary goal was to see if the system could genuinely improve administrative efficiency and transparency. The findings from the data analysis were compelling. The study's results demonstrated that the SIMDEK training had a significant positive effect on improving the understanding of village residents. This was statistically confirmed by an Asymp. Sig (2-tailed) value that was smaller than the significance level α, which is the standard measure for statistical significance. Based on these outcomes, the conclusion is clear: the implementation of SIMDEK can markedly improve the speed of services, the accuracy of data processing, and the transparency of information within Poncokusumo Village. This study holds significant implications, providing a strong case for village governments to expand the use of SIMDEK. Doing so is not just a technological upgrade; it represents a strategic and necessary step toward the broader digital transformation of public services, ensuring a more responsive and accountable local government for the community.